Restaurator. International Journal for the Preservation of Library and Archival Material (De Gruyter, 1970)
Restaurator is the only international periodical specializing exclusively in the conservation of library and archive materials. Articles examine the many important aspects of this subject area, such as technology, practical experience, and organization. They also address scientific fundamentals, including the development of new preservation techniques and improvements to established methods.